THE INFLUENCE OF REDUCTIVE DISSOLUTION OF IRON OXIDES BY S(-II) ON URANIUM MOBILITY - Alexandratos, V. G.; Behrends, T.; Van Cappellen, P. (Bulletin of the Geological Society of Greece, 2010)
This study investigates possible redox transformations of uranium under Ntransient redox conditions. NSpecific focus lies on the fate of U as reductive dissolution of iron oxyhydroxides by S(-II) is initiated. In batch experiments sulfide was incrementally added to a lepidocrocite suspension containing adsorbed U(VI). The partitioning of uranium was monitored during the progressing transformation of lepidocrocite into FeS. Synchrotron-based X-ray absorption spectroscopy was used to resolve the oxidation state of uranium.Upon addition of sulfide intermediate release of U from the solid to the solution was observed. The mobilization of U was followed by immobilization in later stages. XAS reveals that this immobilization coincides with reduction of NU(VI) to U(IV). Consequently, reduction of U(VI) and precipitation of U(IV) solids, due to a shift from oxic to sulfate reducing conditions is possible. NHowever, kinetic effects might lead to an intermediate mobilization of U that should be considered for the risk assessment of nuclear waste repositories and the remediation of sites, contaminated with radionuclides.